(untitled) (Bangladesh Journal of Agricultural Research, 2008)
The study estimated the economic returns to the past investment on the development of two 1PM practices for controlling soil borne diseases in brinjal cultivation in Bangladesh. Economic surplus model with ex-post analysis was used to estimate returns to investment. The study showed that about 20.10% more brinjal production was made available due to adoption of IPM practices (i.e. use of poultry refuse and mustard oilcake) during 2002-2003. The yields of brinjal under IPM practices were 33% and 34% higher, respectively, over the non-IPM practices. Internal rate of return (IRR), net present value (NPV) and benefit cost ratio (BCR) of the past investments were estimated at 26%, Tk. 436.21 million and 3.0, respectively. Under various assumptions on cost and return, the IRR ranged from 20 to 32% and BCR ranged from 2 to 5. The investment in research and development of 1PM practices for managing soil born diseases in brinjal cultivation was found to be very efficient. Key Words: Brinjal, soil borne disease, producer surplus, consumer surplus, ex-post analysis, returns to investment, internal rate of return, net present value doi:10.3329/bjar.v33i3.1605 Bangladesh J. Agril. Res. 33(3) : 459-468, September 2008